Fortaleza em tempo de carnaval: blocos, maracatus e a política dos editais - Cruz, Danielle Maia (2013)
With an ethnographic proposal, this thesis aims to understand the recent changing processes of Fortaleza‟s carnival revels. This relates to a range of policies implemented during Luizianne Lins‟ eight-year municipal administration, particularly between 2009 and 2012. These are changes made in agreement with the state power in order to make, among other purposes, the city attractive to tourists also because of its traditional demonstrations, such as carnival revels. Among the measures taken by Fortaleza City Hall regarding this revelry, the creation of a bidding policy, which consists of funding, is the most interesting due to the aims herein proposed, since it has established a new dynamic on the concession of resources; moreover, the different relationship between revellers and the public power; as well as other festive aspects and revels management. Thereby, taking into account the carnival activities of groups of pre-carnival and maracatu, this thesis tries to understand whether or not the cultural bidding policy interfered on the compositional logic of Fortaleza‟s traditional carnival manifestations and how the revellers reacted to the criteria required by the government. The rationale is if, on one hand, new mechanisms of control of the revels by the public power appeared, on the other hand, revellers recreate, reinvent and reframe their own carnival practice from their own cultural logic and scheme, even if this may occur among negotiations on the projects of changes required. Thus, in theory, the discussion on this thesis falls upon culture and government.